Vegetation Increases CH 4 Emissions and Methanotroph Diversity in Marine Sediments - Marion Dolivet‐Maréchal; Carlos Palacin‐Lizarbe; Henri M. P. Siljanen; Dhiraj Paul; Abigaïl Delort; Jonathan Gervaix; Charline Creuzé des Châtelliers; Sabine Schmidt; Mathis Cognat; David Sebag; Olivier Taugourdeau; Clara Schübert; et al. (Global Change Biology, 2026)
Seagrass meadows are key blue carbon (C) ecosystems, storing large amounts of organic C over centuries. Their climate benefits may be reduced by methane (CH 4 ) emissions, whose microbial and environmental descriptors in Zostera noltii meadows, dominant seagrass in North‐Western Europe, remain poorly understood. We studied CH 4 fluxes, CH 4 ‐producing and consuming microbial communities and sediment physicochemical parameters in Z. noltii meadows and adjacent bare sediments across seven sites in Arcachon Bay, France. In situ CH 4 fluxes were measured at low tide during daytime conditions, providing standardized estimates of peak emissions. Microbial communities were characterized using targeted metagenomics of three functional genes ( mcrA , mmoX , pmoA ) and quantitative PCR. CH 4 fluxes were higher in vegetated than bare sediments (24.4 ± 2.6 vs. 9.4 ± 0.7 μmol m −2 day −1 ). Mixed linear models and random forest analyses identified C accumulation rate and CO 2 flux as the strongest positive descriptors of CH 4 fluxes. Vegetated sediments hosted more diverse methanotrophs, while methanogens showed no habitat differences. Four genera ( mcrA–Methanolobus , mmoX–Methylocella , pmoA–Methylococcus , Methyloglobulus ) emerged as abundant, seagrass‐associated, correlated with CH 4 fluxes, and highlighted by models. Functional diversity, especially pmoA richness, was a stronger microbial descriptor of CH 4 fluxes than gene abundance or a specific genus. Findings indicate Z. noltii meadows enhance C burial and CH 4 emission, with methanotroph diversity potentially mitigating CH 4 emissions. Our results provide the first integrated assessment of CH 4 fluxes and their descriptors in Z. noltii meadows, based on limited temporal coverage capturing the daytime peak emission conditions, highlighting the intertwined nature of C burial and CH 4 emissions and the need to account for both in blue C climate assessments.

Drastic changes in tidal hydrodynamics following seagrass decline and their seasonal variations in a shallow lagoon - Arnaud Le Pevedic; Mathis Cognat; Aldo Sottolichio; Florian Ganthy (Coastal Engineering, 2026)